Tranexamic Acid in Patients Undergoing Liver Resection: An Updated Systematic Review and Meta-Analysis of Randomized Controlled Trials - Mohammad Tanashat MD; Basma Badrawy Khalefa MD; AlMothana Manasrah MD; Husam Abu Suilik MD; Mohamed Abouzid PharmD, PhD; Wafaa Shehada MD; Ahmed Almasry MBBCh; Ibrar Atiq MD; Mohamed Abuelazm MBBCh (Clinical and Applied Thrombosis/Hemostasis)
Background Tranexamic acid (TA), a synthetic lysine derivative, is known for its antifibrinolytic effect and potential to reduce bleeding in surgeries like arthroplasty, cardio-aortic procedures, and liver transplantation. This meta-analysis seeks to provide robust clinical evidence on TA's effectiveness in reducing blood loss and transfusion needs during orthotopic liver transplantation. Methods The systematic review and meta-analysis included the relevant randomized controlled trials (RCTs) retrieved from PubMed, EMBASE, Web of Science, Cochrane, and SCOPUS databases until August 2024. The meta-analysis was done using (RevMan 5.4.1). PROSPERO ID: CRD42024589151. Results Our meta-analysis of seven RCTs with 1875 patients found no significant differences between TA and control groups in total red blood cell units transfused (MD: −3.74 units; 95% CI [−8.49, 1.01]; P  = .12), perioperative transfusions (MD: −0.42 units; 95% CI [−3.17, 2.32]; P  = .76), or overall blood loss (MD: −167.81 mL; 95% CI [−415.29, 79.67]; P  = .18). For safety outcomes, TA was associated with a higher rate of venous thromboembolism events (RR: 1.71; 95% CI [1.01, 2.87]; P  = .05; event rate: 4.89% vs 2.91%), while no significant differences were found in other surgical complications (RR: 1.12; 95% CI [0.92, 1.37]; P  = .26). Conclusion TA does not reduce blood loss or the need for postoperative transfusions in orthotopic liver transplantation and may raise thrombotic risk. Caution is required to interpret these results due to variations in the study/hospital-specific transfusion protocol details. Larger studies are needed to confirm these findings, and future research should explore the effects of multiple dosing regimens on blood loss and transfusion requirements.